ASRGL1 Correlates With Immune Cell Infiltration in Hepatocellular Carcinoma and Can Serve as a Prognostic Biomarker - Xue, Cailin; Gao, Peng; Cui, Xiaohan; Zhang, Xudong; Lei, Jin; Li, Renzhi; Zhu, Chunfu; Qin, Xihu (Frontiers in Oncology, 2021)
Background: L-asparaginase (ASRGL1) is an enzyme that catalyzes the hydrolysis of L-asparagine (Asn) to L-aspartic acid (Asp) and ammonia. Recently, numerous studies have shown the was high correlation between ASRGL1 expression and tumorigenesis. However, the expression and biological function of ASRGL1 in HCC is still unknown. Methods: We explored the mRNA expression of ASRGL1 in HCC using HCCDB, Oncomine and TIMER 2.0 database. Besides, Western blot and immunohistochemical tests were used to uncover the mRNA expression of ASRGL1 in HCC. The LinkedOmics was used to investigate the co-expression genes of ASRGL1, and its regulators including kinases, miRNAs and transcription factors. The Gene Ontology (GO) term and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway of the co-expression genes were also investigated using LinkedOmics. The correlation between the expression of ASRGL1 and immune infiltrates was analyzed using TIMER 2.0 database and GEPIA. The effects of ASRGL1 expression on the patient’s outcome were investigated in the UALCAN, Kaplan-Meier plotter and GEPIA database. The c-Bioportal was used to explore the mutation of ASRGL1 in HCC. Results: ASRGL1 was regulated in HCC tumor compared to the adjacent tissues. The high ASRGL1 expression in HCC indicated poorer relapse-free survival, progression-free survival, disease-specific survival and overall survival. The expression of ASRGL1 had a significant correlation with the infiltrating levels of B cells, CD4+ T cells, macrophages, neutrophils, and dendritic cells in HCC. Conclusion: Our findings suggest that ASRGL1 is over-expressed in HCC and have a significantly correlation with the prognosis and immune infiltration of HCC. Therefore, ASRGL1 may serve as a biomarker for early diagnosis and treatment of HCC.